2018
DOI: 10.3390/s18051380
|View full text |Cite
|
Sign up to set email alerts
|

Social Sentiment Sensor in Twitter for Predicting Cyber-Attacks Using ℓ1 Regularization

Abstract: In recent years, online social media information has been the subject of study in several data science fields due to its impact on users as a communication and expression channel. Data gathered from online platforms such as Twitter has the potential to facilitate research over social phenomena based on sentiment analysis, which usually employs Natural Language Processing and Machine Learning techniques to interpret sentimental tendencies related to users’ opinions and make predictions about real events. Cyber-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…The solution was developed in Python 3 programming language, using Scrapy-An open-source framework [50]. Previous studies [51,52] have used similar technologies to collect big volumes of data automatically in the absence of an API (Application Programming Interface). Article [53] describes in detail the process of data acquisitions, difficulties encountered and solutions to solve them.…”
Section: Data Gathering Processmentioning
confidence: 99%
“…The solution was developed in Python 3 programming language, using Scrapy-An open-source framework [50]. Previous studies [51,52] have used similar technologies to collect big volumes of data automatically in the absence of an API (Application Programming Interface). Article [53] describes in detail the process of data acquisitions, difficulties encountered and solutions to solve them.…”
Section: Data Gathering Processmentioning
confidence: 99%
“…Consequently, organizations are able to make improvements and adopt practices in line with the opinion of their target audience. Online platforms such as Twitter, which generate large amounts of data all the time—constituting a Big Data producer—have the potential to facilitate research over social phenomena based on sentiment analysis [ 5 ], as well as the search for new solutions to help extract useful knowledge from those large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Event prediction and monitoring can then be carried out by applying connective action theory that links a live event with the reactions of users [19]. For example, it has been demonstrated that events with a negative impact on society can motivate hacker activists to perpetrate cyber attacks [20]. Twitter can then be used as an alternative engine for exchanging information related to natural disasters, such as fires, floods, hurricanes, and earthquakes.…”
Section: Introductionmentioning
confidence: 99%